Microfinance Training on MSMEs In Klatak Tourism Village Facing the Covid-19 Pandemic (Indonesian Journal of Devotion and Empowerment, 2022)
Covid-19 has paralyzed the world economy, including Indonesia. Indonesian people can still not face the economic downturn due to the Covid-19 pandemic. Microfinance management for MSME actors in Indonesia is increasingly essential, especially in a pandemic like the current one. Therefore, Microfinance training is needed so MSME actors can survive amid a sluggish economy. This community service program partners with the Masyarakat Peduli Wisata Klatak (Makladuta). The method used is Community Service Workshop. This activity is also in collaboration with the Department of Management FE Unnes, which has made Makladuta a partner. Service activities are carried out online through zoom meetings and Youtube streaming on Tuesday, August 10, 2021. The resource person for the activity is the Head of the Central Java Province Cooperatives and SMEs Office, Dra. Ema Rachmawati, M. Hum., which describes the material on "Steps for Financial Management and Improving MSME Business Creativity." The second resource person is the Founder and CEO of Pentone.id, Yoga Muda Aditya, S.B.A., delivered the material "Financial Literacy and the Importance of Financial Reports in MSMEs." The participants were very enthusiastic about participating in this activity. It can be seen in the participation of participants when the resource person invites direct dialogue with the participants. Participants were also very enthusiastic about the question-and-answer session. Covid-19 telah melumpuhkan perekonomian dunia, tak terkecuali Indonesia. Masyarakat Indonesia masih belum mampu menghadapi penurunan ekonomi akibat adanya pandemic Covid-19. Pengelolaan keuangan mikro bagi para pelaku UMKM di Indonesia semakin penting dirasakan, terlebih dalam kondisi pandemic seperti saat ini. Oleh karena itu, diperlukan pelatihan Keuangan Mikro agar para pelaku UMKM dapat bertahan di tengah lesunya perekonomian. Program pengabdian kepada masyarakat ini bermitra dengan Masyarakat Klatak Peduli Wisata (Makladuta). Metode yang digunakan adalah Workshop Pengabdian pada Masyarakat. Kegiatan ini juga bekerjasama dengan Jurusan Manajemen FE UNNES yang telah menjadikan Makladuta sebagai mitra. Kegiatan pengabdian dilaksanakan secara daring melalui zoom meeting dan streaming YouTube, pada hari Selasa, 10 Agustus 2021. Narasumber kegiatan adalah Kepala Dinas Koperasi dan UMKM Provinsi Jawa Tengah, Dra. Ema Rachmawati, M.Hum. yang memaparkan materi mengenai “Langkah-langkah Jitu Pengelolaan Keuangan dan Peningkatan Kreativitas Usaha UMKM”. Narasumber kedua adalah Founder dan CEO Pentone.id, Yoga Muda Aditya, S.B.A. yang menyampaikan materi “Literasi Keuangan dan Pentingnya Laporan Keuangan pada UMKM”. Peserta kegiatan sangat antusias mengikuti kegiatan ini. Hal ini tampak pada partisipasi peserta saat narasumber mengajak dialog langsung dengan peserta. Peserta juga sangat antusias pada sesi tanya jawab.